Targeting GM-CSF in COVID-19 Pneumonia: Rationale and Strategies - Bonaventura, Aldo; Vecchié, Alessandra; Wang, Tisha S.; Lee, Elinor; Cremer, Paul C.; Carey, Brenna; Rajendram, Prabalini; Hudock, Kristin M.; Korbee, Leslie; Van Tassell, Benjamin W.; Dagna, Lorenzo; Abbate, Antonio (Frontiers in Immunology, 2020)
COVID-19 causes a clinical syndrome ranging from mild symptoms to severe pneumonia that often leads to respiratory failure, need for mechanical ventilation, and death. Most of the lung damage is driven by inflammatory cytokines (interleukin-6, interferon-γ, and granulocyte-monocyte stimulating factor [GM-CSF]). Blunting this hyperinflammation with immunomodulation may lead to clinical improvement. GM-CSF is produced by many cells, including macrophages and T-cells. GM-CSF-derived signals are involved in macrophage differentiation, including alveolar macrophages (AMs). In animal models of respiratory infections, the intranasal administration of GM-CSF increased the proliferation of AMs and improved outcomes. Increased levels of GM-CSF have been recently described in patients with COVID-19 compared to healthy controls. While GM-CSF might be beneficial in some circumstances as an appropriate response, in this case the inflammatory response is maladaptive by virtue of being later and disproportionate. The inhibition of GM-CSF signaling may be beneficial in improving the hyperinflammation-related lung damage in the most severe cases of COVID-19. This blockade can be achieved through antagonism of the GM-CSF receptor or the direct binding of circulating GM-CSF. Initial findings from patients with COVID-19 treated with a single intravenous dose of mavrilimumab, a monoclonal antibody binding GM-CSF receptor α, showed oxygenation improvement and shorter hospitalizations. Prospective, randomized, placebo-controlled trials are ongoing. Anti-GM-CSF monoclonal antibodies, TJ003234 and gimsulimab, will be tested in clinical trials in patients with COVID-19, while lenzilumab received FDA approval for compassionate use. These trials will help inform whether blunting the inflammatory signaling provided by the GM-CSF axis in COVID-19 is beneficial.